Orchestration of Ion Channels and Transporters in Neocortical Development and Neurological Disorders - Bando, Yuki; Ishibashi, Masaru; Yamagishi, Satoru; Fukuda, Atsuo; Sato, Kohji (Frontiers in Neuroscience, 2022)
Electrical activity plays crucial roles in neural circuit formation and remodeling. During neocortical development, neurons are generated in the ventricular zone, migrate to their right position, and elongate dendrites and axons, and form synapses. In this review, we summarize the functions of ion channels and transporters in neocortical development. Then, we discuss links between neurological disorders caused by dysfunction of ion channels (channelopathies) and neocortical development. Finally, we introduce powerful emerging optical techniques for application to physiological studies of neocortical development and pathophysiology of channelopathies.